1991
DOI: 10.1071/rd9910585
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone and follicle stimulating hormone induce premature condensation of chromatin in goat (Capra hircus) oocytes

Abstract: This study tested the hypothesis that premature condensation of chromatin in goat oocytes following superovulation with 1200 i.u. pregnant mare serum gonadotrophin (PMSG) is mediated by the high luteinizing hormone (LH) activity inherent in this gonadotrophin. Goats were treated with either a standard (3.95 mL) or high (7.90 mL) dose of a highly purified follicle-stimulating hormone (FSH) preparation (Ovagen), and different doses of human chorionic gonadotrophin (hCG) were added to increase the level of LH bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…There is some evidence to support this hypothesis. First, we have shown that increasing the level of LH bioactivity during superovulation of goats with FSH, through the administration of subovulatory doses of hCG, resulted in chromatin condensation without nuclear membrane break¬ down (Kumar et al, 1991). Second, Bomsel-Helmreich et al (1989) have found that low doses of hCG initiated chromatin condensation and not germinal vesicle breakdown in rabbit oocytes, whereas with increasing doses of hCG, more advanced stages of nuclear maturation occurred.…”
Section: Discussionmentioning
confidence: 91%
“…There is some evidence to support this hypothesis. First, we have shown that increasing the level of LH bioactivity during superovulation of goats with FSH, through the administration of subovulatory doses of hCG, resulted in chromatin condensation without nuclear membrane break¬ down (Kumar et al, 1991). Second, Bomsel-Helmreich et al (1989) have found that low doses of hCG initiated chromatin condensation and not germinal vesicle breakdown in rabbit oocytes, whereas with increasing doses of hCG, more advanced stages of nuclear maturation occurred.…”
Section: Discussionmentioning
confidence: 91%
“…It implies that the superovulation effect was not boosted up by high and low dosages of exogenous pFSH. In superovulated does, reduced fertility occurred due to prolonged elevation in estrogen concentrations resulting from the large anovulatory follicles and the abnormal maturation of oocytes (Cameron et al, 1988; Kumar et al, 1991; Ryan et al, 1991). Moreover, high estradiol concentration around and/or beyond ovulation induced disorders on the later reproductive process of fertilization and embryo development (Veiga-Lopez et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unfertilised ova may also be attributed to the abnormal maturation of oocytes, due to premature activation of the initial stages of meiotic oocyte maturation. This abnormality usually occurs as a result of increased blood LH concentrations following eCG superovulation treatment -as this hormone exhibits both LH and FSH bioactivity (Cameron et al, 1988 andKumar et al, 1991).…”
Section: Discussionmentioning
confidence: 99%